Barium strontium titanate-based high-entropy energy storage ceramic with core-shell structure and preparation method of barium strontium titanate-based high-entropy energy storage ceramic

By introducing bismuth, sodium and potassium ions into the strontium titanate system to improve the degree of chaos and using SiO2 cladding to shield the electric field, the problem of strontium titanate-based ceramic breakdown under high electric field is solved, and the polarization strength and breakdown field strength are achieved simultaneously, enhancing the energy storage density and reliability of the ceramic.

CN119504256APending Publication Date: 2025-02-25ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411682517.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing strontium barium titanate-based ceramics are prone to breakdown under high electric fields, limiting their energy storage density, and when the second phase is introduced to increase the breakdown field strength, the polarization strength will be weakened.

Method used

By introducing bismuth, sodium and potassium ions into the strontium titanate system, the degree of chaos is increased and the ferroelectric domain size is reduced, thereby improving the polarization strength of the ceramic; at the same time, the SiO2 cladding layer with high breakdown strength is used to coat the high entropy strontium titanate to shield the electric field and improve the breakdown field strength.

Benefits of technology

It achieves the simultaneously improved the polarization strength and breakdown field strength of the ceramic, and improved the energy storage density and service reliability of strontium titanate-based ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504256A_ABST
    Figure CN119504256A_ABST
Patent Text Reader

Abstract

The invention discloses a barium strontium titanate-based high-entropy energy storage ceramic with a core-shell structure, the barium strontium titanate-based high-entropy energy storage ceramic comprises SiO2 serving as a shell part and high-entropy ceramic powder serving as a core part, and the high-entropy ceramic powder comprises barium strontium titanate serving as a main phase and sodium potassium bismuth titanate serving as a high-entropy doping phase. The invention also discloses a preparation method of the barium strontium titanate-based high-entropy energy storage ceramic with the core-shell structure, which comprises the following steps: mixing and dissolving a carbonate raw material of a main phase and carbonate or oxide of a high-entropy doping phase, and stirring to form gel; removing organic components in the gel; calcining to form a perovskite phase to obtain high-entropy ceramic powder; sequentially dispersing in an acidic activator, a weakly acidic buffer agent and a weakly alkaline surfactant, adding a silicon source precursor, and heating to form a coating phase SiO2; and after sintering, annealing to obtain a final product. According to the barium strontium titanate-based high-entropy energy storage ceramic with the core-shell structure, the polarization intensity and the breakdown field strength of the ceramic can be improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage ceramics, and in particular relates to a barium strontium titanate-based high-entropy energy storage ceramic with a core-shell structure and a preparation method thereof. Background Art

[0002] Ferroelectric energy storage ceramics are a type of energy storage device that can quickly store and release electrical energy through polarization reversal. They have broad development prospects in the fields of capacitors, fast charging, solar energy and wind energy storage. The energy storage density of ferroelectric energy storage ceramics is directly related to the maximum polarization intensity, residual polarization intensity, breakdown field strength and other properties of the ceramics. As a typical energy storage ceramic material, barium strontium titanate (Ba 1-x Sr x TiO3) ceramics have adjustable remnant polarization intensity (P r ), coercive field (E c ) and Curie temperature (T c ), which can adapt to the needs of capacitors in different service environments, is an important candidate for lead-free energy storage ceramics. However, due to the band gap of 3.2eV, barium strontium titanate materials are easily broken down under high electric fields, which limits the energy storage density of barium strontium titanate-based ceramics. Therefore, how to improve the breakdown field strength of barium strontium titanate ceramics has become an urgent problem for researchers to solve.

[0003] In the past studies, researchers have introduced a second phase with high breakdown strength (such as SiO2, MgO, Al2O3, etc.) into barium strontium titanate to improve the breakdown field strength of barium strontium titanate-based ceramics, and to a certain extent, improved the energy storage density of barium strontium titanate (such as Chinese patent publication number CN105272217A discloses a preparation method of barium strontium titanate-based alumina composite ceramics with high energy storage density; and Chinese patent publication number CN104725036A discloses a high-temperature, low-loss barium strontium titanate-based energy storage ceramic titanium, with the general formula Ba x Sr 1-x TiO 3+y The melt is represented by, where x represents the molar fraction of the Ba component, 0≤x≤0.5, and y represents the molar fraction of the Ba component of the melt. x Sr 1-x TiO 3+y The mass percentage of the second phase is 0<y≤15%, and the composition of the frit is B2O330~50%, SiO2 15~30%, Bi2O3 15~30%, Al2O3 0~10%, ZrO2 0~10%, BaO0~10%, CaO 0~15%). However, due to the introduction of the second phase, the effective fraction of the polarization phase is inevitably reduced, resulting in a significant weakening of the polarization strength of the ceramic.

[0004] Therefore, how to simultaneously improve the polarization strength and breakdown field strength of ceramics has become a scientific problem that needs to be solved urgently. Summary of the invention

[0005] The object of the present invention is to provide a core-shell structured barium strontium titanate-based high entropy energy storage ceramic and a preparation method thereof, which can simultaneously improve the polarization strength and the breakdown field strength of the ceramic.

[0006] The present invention provides the following technical solutions:

[0007] A barium strontium titanate-based high-entropy energy storage ceramic with a core-shell structure, the barium strontium titanate-based high-entropy energy storage ceramic comprises SiO2 as a shell portion and a high-entropy ceramic powder as a core portion, the high-entropy ceramic powder comprises barium strontium titanate as a main phase and sodium potassium bismuth titanate as a high-entropy doping phase.

[0008] The present invention introduces bismuth, sodium and potassium ions into the A position of the barium strontium titanate system to increase the disorder of the system and reduce the size of the ferroelectric domain, thereby increasing the polarization strength of the ceramic; at the same time, the high entropy barium strontium titanate is coated with a SiO2 coating layer with a high breakdown strength to shield the electric field, thereby increasing the breakdown field strength of the ceramic.

[0009] The chemical composition of the high entropy ceramic powder is (100-x mol%) (Ba 0.4 Sr 0.6 )TiO3-(xmol%)(Bi 0.5 Na 0.25 K 0.25 )TiO3, called BST-BKNT; where the value range of x is 0-100.

[0010] Preferably, the chemical composition of the high entropy ceramic powder is (80 mol%) (Ba 0.4 Sr 0.6 )TiO3-(20mol%)(Bi 0.5 Na 0.25 K 0.25 )TiO3.

[0011] The density of the barium strontium titanate-based high-entropy energy storage ceramic with a core-shell structure is higher than 99.5%, and the particle size is between 100 and 200 nm.

[0012] The present invention also provides a method for preparing the above-mentioned core-shell structured barium strontium titanate-based high entropy energy storage ceramic, the preparation method comprising:

[0013] (1) mixing and dissolving a hydrolysis-inhibiting solvent, a cross-linking agent, an initiator, a carbonate raw material of the main phase, a carbonate or oxide of the high entropy doping phase, a dissolving agent, and an accelerator, and stirring to form a gel;

[0014] (2) removing the organic components in the gel to obtain a black fluffy mass;

[0015] (3) calcining the black fluffy block to form a perovskite phase, thereby obtaining a high entropy ceramic powder, including barium strontium titanate as a main phase and sodium potassium bismuth titanate as a high entropy doping phase;

[0016] (4) dispersing the high entropy ceramic powder in an acidic activator, a weakly acidic buffer and a weakly alkaline surfactant in sequence, adding a silicon source precursor, and heating to form a coating phase SiO2 on the high entropy ceramic powder;

[0017] (5) Sintering the product of step (4), and annealing after sintering to obtain barium strontium titanate-based high entropy energy storage ceramics.

[0018] The preparation method provided by the present invention adopts a sol-gel method to prepare ceramic powder, improves the surface activity of the powder through a three-step liquid phase method, coats a layer of SiO2 on the surface of the powder particles, and sinters the ceramics through discharge plasma, thereby inhibiting the growth of ceramic particles, reducing the loss of energy storage ceramics, and improving energy storage efficiency.

[0019] In step (1), the barium strontium titanate main phase is prepared by a sol-gel method with a barium-strontium ratio of 4:6. After removing the organic components, the block needs to be ground into powder to ensure that the particle size of the ceramic powder after calcination is small enough to increase the breakdown field strength; the doping phase is mixed with the carbonate raw material of the main phase in the form of carbonate or oxide and added to the sol, and is evenly dispersed in the sol by a solvent and an accelerator; since the high entropy doping phase is volatile at high temperature, it is necessary to add 5 mol% of the doping phase to reduce defects in the ceramic, thereby increasing the polarization strength and breakdown strength of the ceramic.

[0020] In step (1), butyl titanate is taken as a Ti source and a cross-linking agent, dissolved in ethylene glycol and stirred until uniformly mixed; citric acid is added to the mixed solution as a solvent, and pure water is added to help the dissociation of the acid and at the same time as an initiator to promote the hydrolysis and cross-linking of butyl titanate; BaCO3, SrCO3, Bi2O3, Na2CO3 and K2CO3 are then added, and concentrated nitric acid is added as an accelerator.

[0021] Preferably, in step (1), the gel is formed by hydrolysis polymerization of butyl titanate to form a network structure, thereby reducing the fluidity of the system and forming a gel state, so the volume fraction of butyl titanate should be controlled at 10-20 vol%.

[0022] The gel is placed at 250-400° C. to remove organic components in the gel; in step (3), it is placed at 800-1100° C. to calcine to form a perovskite phase.

[0023] In step (4), the coating phase is coated on the surface of the high entropy ceramic powder by a three-step liquid phase method, wherein the three-step liquid phase includes an activator, a buffer, a surfactant and a coating phase precursor, and the ceramic powder is ultrasonically dispersed in an acidic activator and then precipitated to remove the surface passivation layer and adsorption layer; the upper clear liquid is removed, and the precipitate is dispersed in a weakly acidic buffer and then precipitated to remove the strong acid on the surface; finally, ultrasonic dispersion is performed in a weakly alkaline surfactant to provide an appropriate amount of highly active hydroxyl groups on the particle surface and improve the bonding strength of the coating phase precursor, thereby improving the breakdown field strength.

[0024] Specifically, the high entropy barium strontium titanate powder is first ultrasonically dispersed in a nitric acid solution, and the surface of the powder is treated with a strong acid to increase the number of unsaturated dangling bonds on the particle surface, thereby increasing the activity of the powder; the powder is allowed to settle naturally and the supernatant is filtered out. A citric acid solution is added, ultrasonically treated, and the supernatant is removed after standing. Dilute ammonia water and anhydrous ethanol are added to the precipitate, ultrasonicated, and stirred; an appropriate amount of tetraethyl orthosilicate is added to the solution to uniformly coat the silicon source precursor on the surface of the high entropy barium strontium titanate ceramic, and heated and stirred until the liquid is completely volatilized. The coated powder is calcined at high temperature to strengthen the binding force between the coating phase and the high entropy barium strontium titanate powder, and a high entropy barium strontium titanate ceramic powder with a core-shell structure is obtained.

[0025] In step (4), the acidic activator is nitric acid, the weakly acidic buffer is citric acid, the weakly alkaline surfactant includes ammonia water and ethanol, and the silicon source precursor is tetraethyl silicate.

[0026] In step (5), sintering is performed using a spark plasma sintering device, and the sintering temperature is slightly higher than the temperature at which the ceramic volume undergoes a second expansion.

[0027] In step (5), the sintering temperature is not lower than 930° C. and not higher than 950° C. to ensure sufficient sintering of the ceramic and inhibit grain growth.

[0028] Preferably, the heating rate should be controlled at 100°C / min before reaching 100°C from the sintering temperature; the heating rate should be controlled at 40°C / min before reaching 20°C from the target temperature; and the heating rate should be controlled at 10°C / min during the last 20°C of heating.

[0029] The step (5) is specifically as follows: after drying the ceramic powder, placing it in a carbon mold containing carbon paper, clamping it with carbon rods of the same diameter at the top and bottom, and sintering it using a discharge plasma sintering device; performing preliminary grinding and polishing on the surface of the sintered ceramic, removing the carbon paper, annealing to eliminate thermal stress and replenishing the oxygen vacancy defects lost in the sintering process in the ceramic, thereby improving the breakdown field strength of the ceramic.

[0030] Compared with the prior art, the present invention has the following benefits:

[0031] The energy storage ceramic based on barium strontium titanate provided by the present invention improves the polarization strength of the ceramic by high entropy doping, and improves the breakdown field strength of the ceramic by coating the ceramic powder with a coating layer with high breakdown strength, specifically: the A position of the barium strontium titanate is co-doped with a donor and an acceptor, which increases the disorder of the system and is more conducive to increasing the polarization strength of the ceramic; SiO2 with high pressure resistance is used as the shell structure, which inhibits the breakdown of the barium strontium titanate and improves the breakdown field strength of the barium strontium titanate-based ceramic.

[0032] The preparation method provided by the present invention uses trivalent Bi and monovalent Na and K to perform donor-acceptor high-entropy co-doping on barium strontium titanate through a sol-gel method, thereby increasing the disorder of the system and thus increasing the polarization strength of the ceramic; in order to reduce the reduction of the ceramic breakdown field strength caused by high-entropy doping, SiO2 with high breakdown strength is used to coat the surface of ceramic particles through a three-step liquid phase activation process, thereby protecting the internal barium strontium titanate-based ceramic particles and preventing the barium strontium titanate from being broken down due to the increase in polarization strength; finally, a barium strontium titanate-based high-entropy ceramic with a density exceeding 99.5% is prepared through discharge plasma sintering, which can have a breakdown strength of 200kV / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of a high entropy coated ceramic sintering process and energy storage density improvement provided by an embodiment of the present invention;

[0034] Figure 2 SEM images of ceramic powder and sintered ceramic provided in the embodiments of the present invention;

[0035] Figure 3 Energy storage density performance diagram of barium strontium titanate before and after doping and coating provided by the embodiment of the present invention:

[0036] Figure 4 Energy storage efficiency performance diagram of the high-entropy barium strontium titanate-based high-entropy energy storage ceramic before and after coating provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0037] Various additional advantages and benefits will become apparent to those of ordinary skill in the art from a reading of the following detailed description of the preferred embodiments.

[0038] Specifically, the chemical composition of the high entropy ceramic powder in the core-shell structured barium strontium titanate-based high entropy energy storage ceramic provided by the embodiment of the present invention is (Ba 0.32 Sr 0.48 Bi 0.1 Na 0.05 K 0.05 )TiO3, the preparation method is specifically as follows:

[0039] (1) Take 34.38 mL of butyl titanate as a Ti source and crosslinking agent, dissolve it in 172 mL of ethylene glycol and stir until it is evenly mixed. Add 38.617 g of citric acid to the solution as a solvent, and add 10 mL of pure water to help the dissociation of the acid, and at the same time as an initiator to promote the hydrolysis and crosslinking of butyl titanate; weigh 6.3785 g of BaCO3, 7.0897 g of SrCO3, 2.3300 g of Bi2O3, 0.2650 g of Na2CO3 and 0.3455 g of K2CO3, and add them together to the above solution. To accelerate the dissolution process of carbonate, add 1 drop of concentrated nitric acid with a mass fraction of 65-68 wt% to the solution every minute, and add a total of 5 drops; after the solution stops bubbling and there are no obvious particles, stir in a 90°C oil bath until the solution turns from white to golden transparent and forms a viscous gel. At this time, the gel is placed at 300°C for 1 hour to remove the organic components in the gel; during this process, the oxidative decomposition of the organic matter makes the gel porous and fluffy, which can effectively reduce the particle size of the ceramic powder after calcination; the black fluffy blocks after calcination are removed, ground for 40 minutes and then calcined at 900°C for 3 hours to form a perovskite phase, thereby obtaining a high-entropy barium strontium titanate ceramic powder.

[0040] (2) First, 5 g of high entropy barium strontium titanate powder was weighed and ultrasonically dispersed in 100 mL of 1 mol / L nitric acid solution for 1 h. The powder surface was treated with strong acid to increase the number of unsaturated dangling bonds on the particle surface, thereby improving the activity of the powder. The powder was allowed to settle naturally for 24 h, and then the supernatant was filtered out. The same volume of 1 mol / L citric acid solution was added and ultrasonically treated for 1 h. After standing for 24 h, the supernatant was removed. 150 mL of concentrated citric acid was added to the precipitate. 6 vol% ammonia water and twice the volume of anhydrous ethanol are added, and the mixture is ultrasonicated for 1 hour and then continuously stirred; 0.4 mL of tetraethyl orthosilicate is slowly added to the solution at a rate of 1 drop per minute to uniformly coat the silicon source precursor on the surface of the high-entropy barium strontium titanate ceramic, and the mixture is stirred in an oil bath at 80°C until all the liquid is evaporated; the coated powder is calcined at 750°C for 3 hours to strengthen the binding force between the coating phase and the high-entropy barium strontium titanate powder, so as to obtain a high-entropy barium strontium titanate ceramic powder with a core-shell structure.

[0041] (3) Take 0.45g of ceramic powder and place it in a carbon mold with an inner diameter of 10mm containing carbon paper, and clamp it with carbon rods of the same diameter at the top and bottom. Use discharge plasma to sinter the barium strontium titanate-based ceramic powder at 930℃ for 5min; after grinding off the surface carbon paper, the sintered ceramic is annealed at 1000℃ for 1.5h to eliminate the stress inside the ceramic and fill the oxygen vacancy defects generated during the sintering process to improve the breakdown field strength of the ceramic; for the annealed ceramic, the thickness needs to be polished to 100-200μm, and gold electrodes are plated on both sides (circular gold electrodes with a sputtering diameter of not less than 2mm on the upper and lower surfaces) for energy storage density testing.

[0042] Among them, in step (3), the heating rate should be controlled at 100°C / min before reaching 100°C from the sintering temperature; the heating rate should be controlled at 40°C / min before reaching 20°C from the target temperature; and the heating rate should be controlled at 10°C / min during the last 20°C heating process.

[0043] Figure 1 A schematic diagram of a high entropy coated ceramic sintering process and energy storage density improvement provided by an embodiment of the present invention; Figure 1 It can be seen that the high-entropy ceramics sintered by spark plasma have a dense structure. The ceramic particles are composed of a core and a shell. The core is BST-BKNT high-entropy grains that provide high polarization performance, and the shell is SiO2 material with high breakdown strength. The combination of the two can jointly improve the energy storage performance of the ceramics.

[0044] Figure 2 The SEM images of the ceramic powder and sintered ceramic provided in the embodiments of the present invention; Figure 2 It can be seen that the ceramic powder prepared by the sol-gel method has a small particle size of about 100 nm, and the energy storage ceramics prepared by the spark plasma sintering method have no obvious pores and high density.

[0045] Figure 3 Energy storage density performance diagram of barium strontium titanate before and after doping and coating provided by the embodiment of the present invention: Figure 3 It can be seen that the high entropy doping method can increase the maximum polarization of BST ceramics from 5.25μC / cm 2 Increased to 19.11μC / cm 2 By coating with SiO2, the breakdown field strength of BST can be increased from 220kV / cm to 250kV / cm. Both methods can improve the energy storage density of BST. High entropy doping and SiO2 coating can combine the advantages of both and further increase the energy storage density of BST to 0.904J / cm 3 The core-shell structured barium strontium titanate-based high entropy energy storage ceramic provided in this embodiment has a maximum polarization strength increased by 120.4% compared to conventional barium strontium titanate ceramics, and the energy storage density of the barium strontium titanate-based high entropy ceramic coated with SiO2 is increased by 83.74% compared to pure barium strontium titanate.

[0046] Figure 4 The energy storage efficiency performance diagram of the high entropy barium strontium titanate-based high entropy energy storage ceramic before and after coating provided by the embodiment of the present invention; Figure 4 It can be seen that after SiO2 coating, the loss of high entropy ceramics is reduced from 0.263J / cm 3 Down to 0.033J / cm 3 , the energy storage efficiency increased from 75.78% to 96.48%.

[0047] In summary, the present invention provides a core-shell structured barium strontium titanate-based high-entropy ferroelectric energy storage ceramic. The donor-acceptor co-doping is carried out in the barium strontium titanate system by the sol-gel method, which significantly improves the maximum polarization strength of the barium strontium titanate-based ceramic. At the same time, the ceramic particles are coated with a SiO2 layer with a high breakdown strength by a three-step liquid phase activation method, which maintains the breakdown field strength of the barium strontium titanate-based high-entropy energy storage ceramic, is more conducive to the tolerance of the barium strontium titanate-based high-entropy ceramic to the service environment, and improves the reliability of the ceramic service. Through the coupling effect of coating and high entropy, the energy storage performance of the barium strontium titanate-based ceramic is further improved.

[0048] Although the preferred embodiments of the present invention have been disclosed for illustrative purposes, those skilled in the art will appreciate that various modifications, additions and substitutions are possible, and thus, the scope of the present invention should not be limited to the above embodiments.

Claims

1. A core-shell structured barium strontium titanate-based high entropy energy storage ceramic, characterized in that: The barium strontium titanate-based high-entropy energy storage ceramic includes SiO2 as a shell and a high-entropy ceramic powder as a core. The high-entropy ceramic powder includes barium strontium titanate as a main phase and sodium potassium bismuth titanate as a high-entropy doping phase.

2. The core-shell structured barium strontium titanate-based high entropy energy storage ceramic according to claim 1, characterized in that: The chemical composition of the high entropy ceramic powder is (100-x mol%) (Ba 0.4 Sr 0.6 )TiO3-(xmol%)(Bi 0.5 Na 0.25 K 0.25 )TiO3, called BST-BKNT; where the value of x ranges from 10-90.

3. The core-shell structured barium strontium titanate-based high entropy energy storage ceramic according to claim 1, characterized in that: The chemical composition of the high entropy ceramic powder is (80 mol%) (Ba 0.4 Sr 0.6 )TiO3-(20mol%)(Bi 0.5 Na 0.25 K 0.25 )TiO3.

4. The core-shell barium strontium titanate-based high entropy energy storage ceramic according to claim 1, characterized in that: The density of the barium strontium titanate-based high-entropy energy storage ceramic with a core-shell structure is higher than 99.5%, and the particle size is between 100 and 200 nm.

5. A method for preparing the core-shell structured barium strontium titanate-based high entropy energy storage ceramic according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) mixing and dissolving a hydrolysis-inhibiting solvent, a cross-linking agent, an initiator, a carbonate raw material of the main phase, a carbonate or oxide of the high entropy doping phase, a dissolving agent, and an accelerator, and stirring to form a gel; (2) removing the organic components in the gel to obtain a black fluffy mass; (3) calcining the black fluffy block to form a perovskite phase, thereby obtaining a high entropy ceramic powder, including barium strontium titanate as a main phase and sodium potassium bismuth titanate as a high entropy doping phase; (4) dispersing the high entropy ceramic powder in an acidic activator, a weakly acidic buffer and a weakly alkaline surfactant in sequence, adding a silicon source precursor, and heating to form a coating phase SiO2 on the high entropy ceramic powder; (5) Sintering the product of step (4), and annealing after sintering to obtain barium strontium titanate-based high entropy energy storage ceramics.

6. The preparation method according to claim 5, characterized in that: In step (1), butyl titanate is taken as a Ti source and a cross-linking agent, dissolved in ethylene glycol and stirred until uniformly mixed, citric acid is added to the mixed solution as a solvent, pure water is added at the same time, BaCO3, SrCO3, Bi2O3, Na2CO3 and K2CO3 are added, and concentrated nitric acid is added as an accelerator.

7. The preparation method according to claim 5, characterized in that: In step (2), the gel is kept at 250-400° C. to remove organic components in the gel; in step (3), the gel is calcined at 800-1100° C. to form a perovskite phase.

8. The preparation method according to claim 5, characterized in that: In step (4), the acidic activator is nitric acid, the weakly acidic buffer is citric acid, the weakly alkaline surfactant includes ammonia water and ethanol, and the silicon source precursor is tetraethyl silicate.

9. The preparation method according to claim 5, characterized in that: In step (5), sintering is performed using a spark plasma sintering device, and the sintering temperature is slightly higher than the temperature at which the ceramic volume undergoes a second expansion.

10. The preparation method according to claim 5, characterized in that: In step (5), the sintering temperature is not lower than 930°C and not higher than 950°C, and annealing is performed at 1000°C after sintering.

Citation Information

Patent Citations

  • Barium strontium titanate / polystyrene core-shell structure and its preparation method

    CN103755848A

  • Preparation method of core-shell-structured dielectric medium ceramic with high energy storage density

    CN105198410A

  • Sodium-bismuth titanate based lead-free piezoelectric ceramic and preparation method thereof

    CN110550953A

  • Water-based gel tape-cast barium strontium titanate textured ceramic and preparation method thereof

    CN111138187A

  • Preparation method of barium strontium titanate-sodium bismuth titanate-based ceramic material for improving temperature stability based on phase change regulation and product thereof

    CN116003123A

Cited By

  • High-entropy perovskite oxide doped ceramic and preparation method thereof

    CN121405461A

  • High-entropy perovskite oxide doped ceramic and preparation method thereof

    CN121405461B